2015
DOI: 10.4049/jimmunol.1302644
|View full text |Cite
|
Sign up to set email alerts
|

Ig Gene Analysis Reveals Altered Selective Pressures on Ig-Producing Cells in Parotid Glands of Primary Sjögren’s Syndrome Patients

Abstract: In this study, we sought to understand the selective pressures shaping the Ig-producing cell repertoire in the parotid glands of primary Sjögren’s syndrome (pSS) patients before and after rituximab treatment (RTX). In particular, we evaluated the role of potential N-glycosylation motifs acquired by somatic hypermutation (ac-Nglycs) within Ig H chain V region (IGHV) genes as alternative selective pressures for B cells in pSS. Five pSS patients received RTX. Sequential parotid salivary gland biopsies were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 50 publications
(63 reference statements)
2
47
0
Order By: Relevance
“…In conclusion, in addition to Vergroesen et al in RA, and our previous work in pSS,2 the meta-analysis described here clearly indicates that there is an increase in ac-Nglycs by somatic hypermutation of immunoglobulin  genes during humoral immune responses in various autoimmune diseases. This phenomenon is thus clearly not restricted to ACPA-expressing B cells in RA as shown by Vergroesen et al .…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In conclusion, in addition to Vergroesen et al in RA, and our previous work in pSS,2 the meta-analysis described here clearly indicates that there is an increase in ac-Nglycs by somatic hypermutation of immunoglobulin  genes during humoral immune responses in various autoimmune diseases. This phenomenon is thus clearly not restricted to ACPA-expressing B cells in RA as shown by Vergroesen et al .…”
supporting
confidence: 81%
“…We have shown previously2 increased numbers of IgG encoding immunoglobulin variable heavy region gene (IGHV) transcripts with ac-Nglycs derived from B cells and plasma cells residing in the inflamed parotid salivary gland of patients with primary Sjögren’s syndrome (pSS) compared with non-pSS sicca controls (24% vs 6%). Importantly, in pSS the IgG encoding transcripts exhibited no evidence for signs of antigen selection in the complementarity determining regions.…”
mentioning
confidence: 99%
“…This is also supported by previous work of the authors on primary Sjögren’s syndrome IgG-BCR sequences 4. The findings presented by Visser et al contribute to the further understanding of the introduction of N- glycosylation sites by autoreactive B cells and its possible impact on selective advantages in B cell selection and/or the breach of tolerance of autoreactive B cells.…”
supporting
confidence: 79%
“…compared with other IgG (auto)antibodies as the result of an increase in IgG Fab glycans (40). Nevertheless, although IgG Fc-glycosylation patterns were associated with disease activity/severity and outcome (41,42) (44). It was suggested that B cell hyperproliferation and selection within the parotid glands may result from Ag-independent interactions of glycosylated BCRs with microbial lectins, as described for lymphoma B cells (see below).…”
Section: Fab Glycosylation During Physiological and Pathological Condmentioning
confidence: 99%